2022
DOI: 10.1002/srin.202200102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of B Segregation at Prior Austenite Grain Boundaries on Microstructures and Toughness in the Heat‐Affected Zone of Mg‐Deoxidized Shipbuilding Steel Plates

Abstract: The effect of B segregation at prior austenite grain boundary (PAGB) on the microstructure and toughness in the heat‐affected zone (HAZ) after high heat input welding at  kJ cm−1 for Mg‐deoxidized shipbuilding steel plates is clarified. With 0.0022 wt.% B addition, B segregation occurs at PAGBs in two forms: solute B and fine Fe23(BC)6 precipitates. B segregation with a concentration of about 4 at.% decreases boundary energy by 0.13 J m−2, which reduces the nucleation density of boundary ferrites by increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…[ 2,3 ] Mg has strong affinity with oxygen and the inclusions in Mg‐treated steel are fine and dispersed. [ 4 ] Our group has studied the effects of Mg contents [ 5 ] and other elements such as Al, [ 6 ] B, [ 7 ] and Nb [ 8 ] on the inclusions, microstructure, and toughness of the HAZ in steel plates with Mg deoxidation. It is confirmed that the composite inclusions in Mg‐treated steels can effectively induce the formation of IAFs and refine austenite grain size.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2,3 ] Mg has strong affinity with oxygen and the inclusions in Mg‐treated steel are fine and dispersed. [ 4 ] Our group has studied the effects of Mg contents [ 5 ] and other elements such as Al, [ 6 ] B, [ 7 ] and Nb [ 8 ] on the inclusions, microstructure, and toughness of the HAZ in steel plates with Mg deoxidation. It is confirmed that the composite inclusions in Mg‐treated steels can effectively induce the formation of IAFs and refine austenite grain size.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Besides, the coarse grains and brittle microstructures will be formed in the coarse-grained heat-affected zone (CGHAZ) during welding process of steel plates, which can deteriorate the HAZ toughness. [5,6] Therefore, improving the welding HAZ toughness is an important factor to obtain high-performance offshore engineering steels.…”
Section: Introductionmentioning
confidence: 99%